On an effective solution of the Riemann problem for third order improperly elliptic equations - S. M. Ali Raeisian (Հայաստանի ԳԱԱ)
The paper considers a boundary value problem for a third order improperly elliptic equation. A numerical method that reduces this problem into six uniquely solvable problems is developed, and the finite differences method is applied to solve the resulting problems.
Keywords: Mathematics; Science; General Works